2020
DOI: 10.1002/2211-5463.12951
|View full text |Cite
|
Sign up to set email alerts
|

A label‐free impedance assay in endothelial cells differentiates the activation and desensitization properties of clinical S1P1 agonists

Abstract: S1P 1 activation maintains endothelial barrier integrity, whereas its desensitization induces lymphopenia. SAR247799, a new G protein‐biased S1P 1 agonist, was compared to clinical stage S1P 1 ‐desensitizing compounds using a label‐free impedance assay assessing endothelial barrier integrity. SAR247799 had the highest activation‐to‐desensitization ratio (114), compared to ponesimod (7.66), ozanimod (6.35), and siponimod (0.170) and thus demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…SAR247799 is a G-protein-biased S1P 1 agonist (inhibiting adenylate cyclase preferentially over activation of β-arrestin and internalization pathways) with endothelial-protective properties in rats and pigs at doses that do not desensitize S1P 1, namely non-lymphocyte-reducing doses. 50,51 In healthy subjects, SAR247799 has an attractive safety, tolerability and pharmacokinetics (PK) profile and the dose-response relationship for lymphocyte pharmacodynamics (PD) has been characterized. 52 Although preclinical studies with SAR247799 showed protective effects in the renal and coronary vasculature in a preventative setting using single doses administered prior to an insult of ischaemia/reperfusion-induced endothelial injury, the effect of chronic administration of SAR247799 on the endothelium is currently unknown.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR247799 is a G-protein-biased S1P 1 agonist (inhibiting adenylate cyclase preferentially over activation of β-arrestin and internalization pathways) with endothelial-protective properties in rats and pigs at doses that do not desensitize S1P 1, namely non-lymphocyte-reducing doses. 50,51 In healthy subjects, SAR247799 has an attractive safety, tolerability and pharmacokinetics (PK) profile and the dose-response relationship for lymphocyte pharmacodynamics (PD) has been characterized. 52 Although preclinical studies with SAR247799 showed protective effects in the renal and coronary vasculature in a preventative setting using single doses administered prior to an insult of ischaemia/reperfusion-induced endothelial injury, the effect of chronic administration of SAR247799 on the endothelium is currently unknown.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In preclinical models, SAR247799 is a biphasic molecule that can activate S1P 1 with endothelial-protective properties at low doses, while causing lymphocyte reduction, like other S1P 1 -desensitizing molecules, at higher doses. 50,51 Biological activities often follow the 4-parameter logistic model in which E max is related to dose (i.e. the bigger the dose, the larger the effect), 53 and with this assumption, many proof-of-concept trials test a single dose, at-or-close-to the maximum tolerated dose.…”
Section: What This Study Addsmentioning
confidence: 99%
“…fingolimod, siponimod and ozanimod) or are in clinical development for immuno-inflammatory disorders, they were all developed as S1P 1 functional antagonists that cause peripheral blood lymphopenia through S1P 1 desensitization. In contrast, SAR247799 is a G-protein-biased S1P 1 agonist, preferentially activating G-protein over β-arrestin and internalization signaling pathways and activates S1P 1 without causing desensitization [15]. SAR247799 thus exhibits endothelial-protective properties without reducing lymphocytes [16].…”
Section: Introductionmentioning
confidence: 98%
“…fingolimod, siponimod and ozanimod) or are in clinical development for immuno-inflammatory disorders, they were all developed as S1P 1 functional antagonists that cause peripheral blood lymphopenia through S1P 1 desensitization. In contrast, SAR247799 is a G-protein-biased S1P 1 agonist, preferentially activating G-protein over βarrestin and internalization signaling pathways and activates S1P 1 without causing desensitization (14). SAR247799 thus exhibits endothelial-protective properties without reducing lymphocytes (15).…”
Section: Introductionmentioning
confidence: 98%
“…Despite efforts to explore the effects of some endothelial-based therapies in the components of HFpEF, there is no confirmation at present that restoring endothelial function would provide clinical improvements in the progression of the components of HFpEF. We therefore set out to test whether 4-week oral treatment with the S1P 1 agonist, SAR247799, a molecule that we have previously shown has endothelial protective effects in animals and humans (14)(15)(16)(17) improves cardiac structural and functional parameters in a rat model of LVH and diastolic function. We used the diabetic Zucker fatty spontaneously hypertensive heart failure F1 hybrid (ZSF1) rat, carrying two separate leptin receptor mutations (fa and facp), which has been described as a genetically-hypertensive, obese and diabetic model of HFpEF (18,19).…”
Section: Introductionmentioning
confidence: 99%